2014
DOI: 10.1186/1472-6882-14-369
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial steroidal saponin and oleanane-type triterpenoid saponins from Paullinia pinnata

Abstract: BackgroundPaullinia pinnata L. (Sapindaceae) is an African woody vine, which is widely used in traditional medicine for the treatment of human malaria, erectile dysfunction and bacterial infections. A phytochemical investigation of its methanol leaf and stem extracts led to the isolation of seven compounds which were evaluated for their antimicrobial properties.MethodsThe extracts were fractionated and compounds were isolated by chromatographic methods. Their structures were elucidated from their spectroscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…Additionally, the leaves were found to contain a cardiotonic tannin [22], ceramides and cerebrosides [23], several triterpenoids, l-quebrachitol, a trioxaphenanthrenone [20], and two unusual flavone glycosides [24]. Oleanane-type triterpenoid saponins with antibacterial and antifungal properties have been isolated from the stem [25,26].…”
mentioning
confidence: 99%
“…Additionally, the leaves were found to contain a cardiotonic tannin [22], ceramides and cerebrosides [23], several triterpenoids, l-quebrachitol, a trioxaphenanthrenone [20], and two unusual flavone glycosides [24]. Oleanane-type triterpenoid saponins with antibacterial and antifungal properties have been isolated from the stem [25,26].…”
mentioning
confidence: 99%
“…All samples contained steroid/triterpenoid. Some research showed that flavonoid, saponin, alkaloid, and steroid/triterpenoid had antibacterial activity [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these phytochemicals are responsible for the stabilization of AgNPs. Several earlier reports correlated the plant phytochemicals with their bioactive attributes and reported the antibacterial and free radical scavenging activities of the phytochemical constituents (Ali et al, 2002;Dahija et al, 2014;Medini et al, 2014;Mohammed et al, 2014;Lunga et al, 2014). The quantity of phytochemical components may vary with the plant part, leaf and stem (Patra et al, 2011).…”
Section: Discussionmentioning
confidence: 99%